A body that stages resistance: dissident visualities and vocalities in the art of Jup do Bairro (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The article explored the resistances staged by Jup do Bairro in her experimental and transfeminist art, highlighting her dissident visualities and vocalities. Through an analysis of her work, with an emphasis on the 'Transgressão' music video, it was investigated how Jup used the crossroads as a reference to destabilize hegemonic representations and create new forms of subjectivity and existence. The writing engaged with concepts of artivism, autonarrative, and anamnesis, identifying in Jup an aesthetic and political response to the oppressions and silencings faced by trans, black, and peripheral bodies, underlining the intersectionality of these issues.
Keywords: experimental art; transfeminism; resistance; dissident visualities; peripheral bodies